Pengobatan Medis oleh Perawat dan Bidan dalam Manajemen Terpadu Balita Sakit - Aloysius Tri Joehanto (Jurnal Hukum dan Etika Kesehatan, 2021)
This study analyzed a normative legal research on conflict resolution of norms of legislation related to the implementation of Integraded Management of Childhood Illness abbreviated as IMCI or Manajemen Terpadu Balita Sakit abbreviated as MTBS which discusses two problem fornulations, namely: first, are nurses and midwives have authority to conduct medical treatment in the application of MTBS? Second, what are the juridical consequences of medical treatment by nurses or midwives in the application of MTBS? This research uses a statue approach and conceptual approach. Nurses and midwives do not have the authority to provide medical treatment in the application of MTBS on the basis of Permenkes Nomor 25 Tahun 2014 tentang Upaya Kesehatan Anak Pasal 25 ayat (2) dan ayat (3) that MTBS is performed by trained nurses and midwives and in its implementation should be supervised by the doctors who have been trained, as this may lead to conflict of norms of existing legislation because of the authority to make clinical decisions based on the diagnosis of a disease and medical treatment efforts in the application of MTBS is the authority of the medical or doctor as regulated in Undang-Undang Nomor 29 Tahun 2004 tentang Praktik Kedokteran Pasal 35 ayat (1). Health workers in carrying out practices should be conducted in accordance with the authority based on their competence to ensure legal certainty and sense of justice in order to improve the welfare of the community. On the one hand providing protection for doctors, nurses and midwives and on the other hand provides protection also for users of health services to achieve a quality service, safe, non-discriminatory and remain affordable.